ANALISIS DAMPAK INVESTASI SOSIAL PT PERUSAHAAN GAS NEGARA TBK DIUKUR MENGGUNAKAN SOCIAL RETURN ON INVESTMENT (STUDI KASUS PROGRAM BANK SAMPAH) - Bonifasius Santiko Parikesit; Sigit Tri Hartanto; Rio Zakarias Widyandaru; Dien Yudithadewi (Politeknik Negeri Malang, 2023)
This paper intends to examine the impact of PT Perusahaan Gas Negara Tbk's social investment, particularly in the waste bank program during the 2020-2021 period in Tembesi Village, Sagulung Sub District, Batam City, Riau Islands Province. The research design used mixed methods, where primary data collection was conducted through interviews with 34 relevant stakeholders from beneficiaries, government and companies. Secondary data is sought through literature studies from journals, books and other relevant sources, both physically and digitally. Using the stages of the Social Return On Investment process, the researchers carried out the process of identifying inputs, activities, outputs, outcomes and impacts, including monetizing in rupiah. Specifically for impact, the analysis was carried out using the Sustainability Compass which was introduced by Herman Daly, and then further developed by Alan Atkisson. The results show the SROI ratio in 2020 is 1: 4.09 and 2021 is 1: 4.76. The positive impact created by the program shows that social investment is effective in fulfilling the agenda of sustainable development goals no. 1 without poverty, no. 3 healthy living, no. 5 gender equality, no. 6 clean water and proper sanitation, and no.17 partnership to achieve goals.